Redox regulation of calcium release in skeletal and cardiac muscle - CECILIA HIDALGO (Biological Research, 2002)
In skeletal and cardiac muscle cells, specific isoforms of the Ryanodine receptor channels mediate Ca2+ release from the sarcoplasmic reticulum. These channels are highly susceptible to redox modifications, which regulate channel activity. In this work, we studied the effects of Ca2+ (endogenous agonist) and Mg2+ (endogenous inhibitor) on the kinetics of Ca2+ release from sarcoplasmic reticulum vesicles isolated from skeletal or cardiac mammalian muscle. Native skeletal vesicles exhibited maximal stimulation of release kinetics by 10-20 µM [Ca2+], whereas in native cardiac vesicles, maximal stimulation of release required only 1 µM [Ca2+]. In 10 µM [Ca2+], free [Mg2+] < 0.1 mM produced marked inhibition of release from skeletal vesicles but free [Mg2+] 0.8 mM did not affect release from cardiac vesicles. Incubation of skeletal or cardiac vesicles with the oxidant thimerosal increased their susceptibility to stimulation by Ca2+ and decreased the inhibitory effect of Mg2+ in skeletal vesicles. Sulfhydryl-reducing agents fully reversed the effects of thimerosal. The endogenous redox species, glutathione disulfide and S-nitrosoglutathione, also stimulated release from skeletal sarcoplasmic reticulum vesicles. In 10 µM [Ca2+], 35S-nitrosoglutathione labeled a protein fraction enriched in release channels through S-glutathiolation. Free [Mg2+] 1 mM or decreasing free [Ca2+] to the nM range prevented this reaction. Possible physiological and pathological consequences of redox modification of release channels on Ca2+ signaling in heart and muscle cells are discussed